Quantum Cryptography for Secure Communications and the Enhancement of U.S. Cybersecurity in the Quantum Age - Hasan, Mahmud (Advances in Social Sciences Research Journal, 2024)
This paper explores the critical role of quantum cryptography in enhancing U.S. cybersecurity, focusing on its potential to counteract the growing threats posed by quantum computing. As quantum computers advance, classical encryption methods like RSA and AES face unprecedented vulnerabilities. Quantum Key Distribution (QKD) offers a groundbreaking solution by leveraging quantum mechanics to secure data transmission. The paper evaluates current implementations and future challenges of quantum cryptography, emphasizing its importance for government, military, financial, and healthcare sectors in safeguarding sensitive communications in the quantum age.